PENGARUH PENERAPAN PEER ASSESSMENT MELALUI MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM KOLOID - Rudi Rudi; Herlina Apriani; Rr Ariessanty Alicia (Vidya Karya, 2018)
Abstract. This study aimed to examine the effectiveness of the application of peer assessment through mind mapping on student learning outcomes in the topic of colloidal system. This quasi-experimental study was conducted at the Madrasah Aliyah Raudhatussyuban with two classes as the research sample, namely the MIA 1 class as the experimental class and the MIA 2 class as the control class. The data collection technique uses 25 questions of objective tests with 5 options. The research data collected was analyzed using the Mann Whitney U test with the help of SPSS. The results of data analysis show that there is an effect of applying peer assessment through mind mapping on student learning outcomes.  Keywords: Learning outcomes, peer assessment, mind mapping, colloidal system. Abstrak. Penelitian ini bertujuan untuk menguji efektivitas penerapan peer assessment melalui mind mapping terhadap hasil belajar siswa pada materi sistem koloid. Penelitian quasi experiment ini di Madrasah Aliyah Raudhatussyuban dengan melibatkan 2 kelas sebagai sampel penelitian, yaitu kelas MIA 1 sebagai kelas eksperimen dan kelas MIA 2 sebagai kelas kontrol. Teknik pengumpulan data menggunakan tes obyektif berjumlah 25 nomor dengan 5 pilihan jawaban. Data penelitian yang terkumpul dianalisis menggunakan uji mann whitney u dengan bantuan SPSS. Hasil analisis data menunjukkan bahwa terdapat pengaruh penerapan peer assessment melalui mind mapping terhadap hasil belajar siswa. Kata Kunci: Hasil belajar, peer assessment, mind mapping, sistem koloid.